Postcare for Repairing Nerve and Tendon Injury Based on Biomimetic Nano-Parallel Material Composite Protein - Junxia Fu; Xiaohong Tan; Yan Tang (Advances in Materials Science and Engineering)
Natural tendons are composed of ordered parallel arrangement of bundles of type I collagen fibers. It is responsible for transmitting the forces generated by the bones and muscles to move the body. Tendon injuries are common sports injuries, accounting for 50% of sports injuries. In adulthood, factors such as few tendon tissue cells and poor blood supply make it difficult to heal on their own after injury. Therefore, restoring the structure and function of native tendon tissue is still an unsolved problem. The purpose of this study is to study the use of biomimetic nano-parallel material composite proteins to induce the directional differentiation of stem cells to tendon lineages to promote muscle regeneration and repair. This study proposes to prepare composite protein nanomaterials by simulating the parallel arrangement of tendon collagen fibers. This can facilitate the directed differentiation of fibroblasts into tendon lineages. It can use the BP algorithm in the neural network algorithm to simulate the parallel arrangement of tendon collagen fibers, which is more efficient than other schemes. The experimental results in this study show that the rat cells are repaired after about 6 weeks. Tendon repair enters a remodeling phase with reduced cell numbers, collagen, and mucopolysaccharide synthesis. During this period, tendon repair gradually changes from the cellular level to the tissue level, and tenocyte metabolism remains high. Tenocytes and collagen fibers are aligned in the direction of stress. A higher proportion of collagen 1 synthesis occurs during this period. Collagen 1 accounts for 65% to 80% of the dry weight of the tendon, which plays the most important role in the mechanical properties of the tendon.